ANALYSIS OF AMINO ACIDS IN LEAF, ROOT AND STEM OF LONICERA NUMMULARIFOLIA PLANT (Scientific journal of the Fergana State University, 2025)
In this article, the quality and quantity of amino acids in the root, leaf and stem of Lonicera nummularifolia growing in Chodak district of Namangan region were studied by high performance liquid chromatography method. Amino acids in the samples were determined using HPLC Agilent technologies DAD 1200 detector.  The amount of amino acids was analyzed structurally in the root, leaf and stem of the plant.